The Effect of Dates Juice on The Bleeding Time An Experimental Study of Male Wistar Strain Rats that Induced by Aspirin. - Sari, Rachma Purnama; Sampurna, Sampurna; Pertiwi, Danis (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Juice of dates (Phoenix dactylifera) is widely used to reduce the risk of spontaneous bleeding by shorting the bleeding time, for example on hemorrhargic fever and the consequence of consuming drugs (e.g. aspirin, anti coagulant, anti cancer, diuretic, etc). This study aimed to investigate the effect of dates juice on the bleeding time of male Wistar strain rats that induced by aspirin. This study was experimental research with post test only control group design. In this study, 10 male Wistar strain rats were randomly divided into 2 groups. The first group (positive control) were only treated by aspirin and the second group (treatment group) were treated by aspirin and palm dates juice. Mean of the bleeding time in first group was 42,6 + 11,5 seconds and in second group was 28,0 + 3,0 seconds. Distribution of data was normal but not homogenous, so that data was analyzed by non parametric statistic test Mann-Whitney. The result showed that there was significant difference between the first and the second group. This study concluded that juice of dates affects the bleeding time of male Wistar strain rats that induced by aspirin.